The Role of Indonesian Language in Developing Critical Thinking Skills of Junior High School Students 16 Jambi City - Darwin, David; Saputra, Dedi Gunawan (PT. Hafasy Dwi Nawasena, 2024)
This study aims to examine the role of Indonesian language learning in developing students' critical thinking skills at SMP 16 Jambi City. Using a qualitative approach, this study explores how Indonesian language learning can contribute to developing critical thinking skills through direct interaction with students and teachers. Data were obtained through interviews, observations, and document analysis, which were then analyzed to identify relevant patterns and themes. The results of the study indicate that Indonesian language learning has great potential in developing students' critical thinking skills. Learning strategies such as the use of texts, discussions, debates, and argumentative writing have proven effective in improving critical thinking skills. Students are trained to identify main ideas, evaluate arguments, and design coherent and evidence-based argument structures. However, there are several obstacles faced, such as time constraints and differences in student motivation in participating in literacy activities. Therefore, further efforts are needed to overcome these obstacles, such as teacher training, providing relevant teaching materials, and utilizing digital technology. With a more holistic approach, Indonesian language learning can be a more effective tool in developing students' critical thinking skills, which contributes to improving the overall quality of education.